Crustal thickness variations in the Eastern Mediterranean and southern Aegean region. (November 2016) - Bilim, Funda; Aydemir, Attila; Ates, Abdullah
Abstract: In this paper, regional analog gravity anomaly map obtained from the General Directorate of Mineral Research and Exploration (MTA) was digitized and used for the calculation of the crustal thickness (Moho depth) variations in the Eastern Mediterranean and the southern part of the Aegean Region. In the gravity anomaly map, there are mainly E–W trending apparent gravity anomalies represented by the contours up to 150 mGal. They are generally parallel to the shorelines of Africa, Turkey and Crete. Crustal thickness variations were calculated from the gravity anomalies, using an empirical equation in this study. Obtained thicknesses (Moho depths) were mapped and correlated with the previous investigations and seismological findings. According to the estimations, crustal thicknesses are about 25–30 km along the coastal regions and more than 30 km on the onshore part of Turkey increasing up to 42 km through the eastern Anatolia. However, there are thin crustal zones around 17 km in the offshore Egypt, to the NW part of Cyprus and about 19 km to the north of Crete. They may be related with the main tectonic trends in this region except the circular thinning to the south of Kas (southwestern part of Turkey). In order to determine the locations and boundaries of prominent tectonic elements, Analytic Signal (AS) and maxspots maps of the gravity anomalies were also prepared in this study. All produced maps are generally consistent to each other and the boundaries of main tectonic units were apparently illustrated in the maxspots map from the horizontal gradient of Bouguer anomalies. Highlights: There are mainly E–W trending gravity anomalies in Eastern Mediterranean. There are thin crustal zones about 17 km in the offshore Egypt and to the NW Cyprus. Thin zones are related with the main tectonic trends except one to the south of Kas. Analytic Signal and maxspots maps of the anomalies were also prepared in this study. All produced maps are consistent to each other and main tectonic units in the area.